Effect of rubber tyre granules on concrete strength and the microstructure characteristics of rubberized concrete - Jusli, Euniza (2015)
The influence of using rubber tyre granules (RTG) as aggregates on the strength of concrete and microstructure characteristics of rubberized concrete was investigated in this study. Mix proportion of cement: sand: aggregate: superplasticizer; 1:1.5:1.7:0.003 and 0.47 water cement ratio (w/c) was used. The RTG of size 1-4 mm and 5-8 mm were used throughout this study. Progressive reduction of strength was observed with the increased of RTG percentage and size. Thermogravimetry and differential thermogravimetric (TGA-DTA) analyses were performed to evaluate the decomposition process of materials heated up to 1000 oC. Less reactions the structure bonds are less at the range of 2000-3000 cm-1 wavelength were detected in Fourier Transform Infra-Red (FTIR) analysis due to the stability of the structures developed in concrete samples. In general, the main elements were calcium, carbon, silica and aluminum. The existence of SBR and carbon black of RTG in the sample can be observed by the presents of a carbon peak in EDX.